2013
DOI: 10.1093/ckj/sfs178
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of community-acquired acute kidney injury in developing countries: analysis of 2405 cases in 26 years from eastern India

Abstract: BackgroundThe epidemiology of acute kidney injury (AKI) differs from country to country and varies from center to center within a country. Owing to the absence of a central registry, data on overall epidemiology of AKI are scanty from India.MethodsThis study aimed at describing changes in epidemiology of community-acquired AKI (CAAKI) over a time span of 26 years in two study periods, namely, 1983–95 and 1996–2008.ResultsWe studied 2405 (1375 male and 1030 female) cases of AKI in the age range 1–95 (mean: 40.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
(45 reference statements)
8
37
2
Order By: Relevance
“…Other reason included late presentation, etiologic factor (septic choc, multi organ involvement due to nephrotoxic). We found an overall mortality rate of 31.5%, within the range of 10-50% found in tropic literature [3,5,[17][18][19]. Half of patient who die need dialysis but could not beneficed of renal replacement therapy, suggest the impact of limited resources on survival.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Other reason included late presentation, etiologic factor (septic choc, multi organ involvement due to nephrotoxic). We found an overall mortality rate of 31.5%, within the range of 10-50% found in tropic literature [3,5,[17][18][19]. Half of patient who die need dialysis but could not beneficed of renal replacement therapy, suggest the impact of limited resources on survival.…”
Section: Discussionsupporting
confidence: 70%
“…Infection was the main etiologic factor in our study as reported by Chijioke in Nigeria [3] and Jai P in India [5] .Toxic, mainly herbal remedies, is also a common cause of AKI in tropic [4,[6][7][8], we found it in 21 patients (19.5%) with 13 due to herbal concoction. Common nephrotoxic find in Africa included impila (callilepsis laureola), violet tree (securidaca longepedunculata) and cap aloes [4,[6][7][8].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In developing countries, acute glomerulonephritis (GN) remains an important cause of AKI and accounts for 9 to 10% of cases of total AKI and is mainly post-infectious in origin [16]. In our study accounted for about 8% of AKI cases, in agreement with regional and international data.…”
Section: Discussion In Relation To Other Studiessupporting
confidence: 90%
“…In hospitals, AKI becomes an important complication when associated with the number and severity of co morbidities experienced by the patients, occurring in a rate around 20% to 40%. 10 Several studies show an increase in its incidence over the last decade. A summary of exiting studies is given in Table- In our study, the most frequent underlying cause requiring hospital admission was a respiratory tract disease observed in 153 (39.9%) patients followed by hepatobiliary diseases (26.4%), infections (23.8%) and diabetes (9.9%).…”
Section: Discussionmentioning
confidence: 99%